Bidirectional Regulation of Hippocampal Synaptic Plasticity and Modulation of Cumulative Spatial Memory by Dopamine D2-Like Receptors - Caragea, Violeta-Maria; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2022)
Dopamine is a key factor in the enablement of cognition and of hippocampal information processing. Its action in the hippocampus is mediated by D1/D5 and D2-like (D2, D3, D4) receptors. While D1/D5-receptors are well recognized as strong modulators of hippocampal synaptic plasticity and information storage, much less is known about the role of D2-like receptors (D2R) in these processes. Here, we explored to what extent D2R contribute to synaptic plasticity and cumulative spatial memory derived from semantic and episodic-like information storage. In freely behaving adult rats, we also assessed to what extent short and long-term forms of synaptic plasticity are influenced by pharmacological activation or blockade of D2R. Antagonism of D2R by means of intracerebral treatment with remoxipride, completely prevented the expression of both short-term (>1h) and long-term potentiation (>4h), as well as the expression of short-term depression (STD) in the hippocampal CA1 region. Scrutiny of involvement of D2R in spatial learning revealed that D2R-antagonism prevented retention of a semantic spatial memory task, and also significantly impaired retention of recent spatiotemporal aspects of an episodic-like memory task. Taken together, these findings indicate that D2R are required for bidirectional synaptic plasticity in the hippocampal CA1 region. Furthermore, they are critically involved in enabling cumulative and episodic-like forms of spatial learning.